FRI0169 ANTINUCLEAR ANTIBODY SEROCONVERSION DURING FOLLOW-UP IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Gualtierotti, R.; Frontini, G.; Pregnolato, F.; Messa, P.; Moroni, G.; Meroni, P. L.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by the presence of autoantibodies and a variable spectrum of clinical manifestations and disease severity. The 2019 criteria for SLE classification by the American College of Rheumatology and European League against Rheumatism define ANA positivity by immunofluorescence or by an equivalent solid-phase assay as the entry criterion (1). However, the prevalence of ANA positivity and the reliability of solid-phase assays in SLE are still a matter of controversy (2). Furthermore, the significance of ANA negativisation during follow-up is uncertain (3). Objectives: Our aim was to retrospectively analyse data on the frequency of ANA seroconversion during the follow-up in a cohort of SLE patients with renal involvement. Methods: Adult patients independent of age at SLE onset with a follow-up duration of at least 36 months starting from January 2009 (for standardization of ANA measurement) and with at least one ANA measurement per year were included in this retrospective longitudinal study. Data on demographic, clinical and laboratory characteristics of the study population are reported in table 1 . ANA have been measured with Hep2 cell immunofluorescence assay. Results: A total of 121 SLE subjects with renal involvement were enrolled. Mean follow-up ± standard deviation (SD) was 8 ± 2 years. Ten subjects (8.3%) with positive ANA at the beginning resulted ANA negative at the end of the follow-up. These subjects had different initial ANA titres: 1:1280 (n=1), 1:640 (n=2), 1:320 (n=2), 1:160 (n=3) and 1:80 (n=2); 48 subjects (39.7%) showed a decrease in ANA titre. Of the 9 patients (7.4%) that were negative at the beginning of follow-up, 6 remained negative, whereas 3 showed ANA positivity at the end of the follow-up with ANA titres 1:160 (n=2) and 1:320 (n=1). No differences between subjects with and without ANA titre variations in terms of age (p=0.551), disease duration (p=0.786), SLEDAI at the beginning (p=0.453) and at the end of follow-up (p=0.169) were observed. ANA negativisation and titre variations at the end of follow-up did not correlate with any of the treatments taken during follow-up, including a history of cyclophosphamide (p=0.788). Conclusion: In our cohort of patients with SLE and renal involvement, 10% of patients experienced negativisation and around 40% of patients showed a decrease in ANA titre during follow-up, independent of disease characteristics and previous treatment. Further studies are warranted to clarify the underlying mechanisms and clinical significance of ANA seroconversion and titre variation in SLE patients. However, based on our results, ANA positivity seems to be a relatively stable parameter further supporting its use as an entry classification criterion for SLE. References: [1]Aringer M et al. Arthritis Rheumatol. 2019; 71(9):1400-1412. [2]Pisetsky DS et al. Autoimmun Rev. 2019; 18(12):102400. [3]Frodlund M et al. Clin Exp Immunol. 2019. Epub ahead of print. Disclosure of Interests: None declared